High-Performance Sport - Nitzsche N; Schulze R; Weigand F; Hummer N; Schulz H (Dynamic Media Sales Verlag, 2018)
Blood flow restrictionin resistance training reduces arterial blood supply. This results in increased metabolic stress in the muscles. The aim of the study was to compare the lactate concentration of acute resistance training under muscle compression at different intensities using the leg press. Eight male subjects (age 24.62 2.73 years, BMI 23.83 0.89 kg*m-2) performed resistance training on three different days (30% of the 1 RM without blood flow restriction = K30, 30% of 1 RM with blood flow restriction = 30BFR, 50% of 1 RM with blood flow restriction = 50BFR) in a randomized order (5 sets, 15 repetitions, 1 minute break between sets) on the leg press. In Rest (R), during (Se1 to SE5), and up to 15 minutes after loading (PO), capillary blood samples were taken to determine lactate levels. The contrast analyzesshowed statistically significant differences for all comparisons of the loading phase (SE1 to SE5) and the PO. The contrast of Lamax(K30: 1.78 0.86 mmol * l-1 vs. 30BFR: 3.43 1.37 mmol * l-1; 30BFR: 3.43 1.37 mmol * l-1 vs. 50BFR: 7.22 2.32 mmol * l-1) across the three conditions showed increasing values of K30 to 50BFR (t = 7.753, p<0.001, g = 2.741). Resistance training on the leg press with blood flow restriction without pressure control showed significant differences in lactate concentration with low to moderate loads than without BFR. KEY WORDS: Exercise Method, Occlusion, BFR, Blood Lactate, Leg Press